Tubal choriocarcinoma presented as ruptured ectopic pregnancy: a case report and review of the literature - Xu, Shengjie (World J Surg Oncol, 2020)
BACKGROUND: Tubal choriocarcinoma is an extremely rare but highly malignant trophoblastic tumor, which may be either gestational or non-gestational in origin. Due to atypical clinical manifestations and symptoms similar to ectopic pregnancy, it is easily to be confused with ectopic pregnancy. In addition, inadequate understanding of this rare disease by clinicians often leads to misdiagnosis or missed diagnosis, which in turn results in delayed treatment or even tumor metastasis. CASE PRESENTATION: This report summarized a case of a woman who was finally diagnosed as tubal choriocarcinoma through the follow-up of serum β hCG levels and histopathological results after undergoing salpingectomy for being misdiagnosed as ectopic pregnancy. Five courses of adjuvant chemotherapy (5-fluorouracil, actinomycin-D, vinorelbine regime) have been administered to the patient in the prevention of any recurrences. During 1-year follow-up, the patient was asymptomatic and presented no evidence of recurrence. CONCLUSIONS: Tubal choriocarcinoma is easily to be confused with ectopic pregnancy. By analyzing this case and previous related cases, we aimed to provide references for clinicians in the diagnosis and treatment of tubal choriocarcinoma.